The effects of transitional care intervention on health outcomes in burn patients: a systematic review and meta-analysis - Sun, Xiangling; Ding, Zhaohong; Yi, Kang; Zhang, Li; Hao, Shuyun; Wu, Manli; Li, Lingling (Frontiers in Rehabilitation Sciences, 2026)
BackgroundBurn patients often face challenges such as discontinuity of care, high risk of complications, and psychological adaptation difficulties after discharge. Transitional care is a critical measure to ensure their safe transition across different healthcare settings. This study employs a meta-analysis to comprehensively evaluate the impact of transitional care interventions on health outcomes in burn patients, providing evidence to support improved continuity of care.MethodsEMBASE, the Cochrane Library, PubMed and Web of Science were searched from the establishment of the databases to July 2025. All analysis were conducted using the Revman 5.3.ResultsA total of 4 randomized controlled trials were included in our meta-analysis, encompassing 281 burn patients, with 141 receiving transitional care interventions and 140 receiving usual care. The meta-analysis revealed that transitional care could significantly enhance the quality of life among burned patients [MD = 26.82, 95% CI (4.25, 49.39), p = 0.02], and mental health [MD = −16.57, 95% CI (−25.36, −7.78), p < 0.001].ConclusionTransitional care has been shown to effectively improve patients’ quality of life and improve emotional well-being. Future studies should integrate both subjective reporting and objective assessment metrics to further validate the independent effects and synergistic interactions of distinct intervention modules within transitional care frameworks.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/ PROSPERO CRD420251042795.